2004
DOI: 10.1074/jbc.m407195200
|View full text |Cite
|
Sign up to set email alerts
|

Structural, Thermodynamic, and Kinetic Analyses of Tetrahydrooxazine-derived Inhibitors Bound to β-Glucosidases

Abstract: The understanding of transition state mimicry in glycoside hydrolysis is increasingly important both in the quest for novel specific therapeutic agents and for the deduction of enzyme function and mechanism. To aid comprehension, inhibitors can be characterized through kinetic, thermodynamic, and structural dissection to build an "inhibition profile." Here we dissect the binding of a tetrahydrooxazine inhibitor and its derivatives, which display K i values around 500 nM. X-ray structures with both a ␤-glucosid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 29 publications
0
19
0
Order By: Relevance
“…The glucose of the incoming substrate has sometimes been observed to be distorted into a 1 S 3 skew boat as it moves toward the 4 H 3 half-chair shape in the first transition state, although in other structures it is poorly defined by the electron density, apparently due to high mobility [108][109][110][111][112]. The structures of certain putative transition state mimics have also been solved in the active site and shown to have a structure close to the 4 H 3 half-chair, although others appeared to inhibit by mechanisms other than transition state mimicry [108,[113][114][115][116][117][118].…”
Section: Catalytic Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…The glucose of the incoming substrate has sometimes been observed to be distorted into a 1 S 3 skew boat as it moves toward the 4 H 3 half-chair shape in the first transition state, although in other structures it is poorly defined by the electron density, apparently due to high mobility [108][109][110][111][112]. The structures of certain putative transition state mimics have also been solved in the active site and shown to have a structure close to the 4 H 3 half-chair, although others appeared to inhibit by mechanisms other than transition state mimicry [108,[113][114][115][116][117][118].…”
Section: Catalytic Mechanismsmentioning
confidence: 99%
“…In the second, deglycosylation step, the catalytic base (the same carboxylate as the catalytic acid) extracts a proton from a water molecule, improving its nucleophilic power to attack at the anomeric carbon and displace the enzyme. Hydrolysis by either mechanism is equivalent in the organism, since mutarotation of the released glucose will lead to a racemic mixture of glucose in solution after a short time rather similar and broad substrate specificities, the complexes of b-glycosidase S from the archaeon Sulfolobus solfataricus and b-glucosidase A from the eubacteria Thermotoga maritima with a range of inhibitors has provided a wealth of information on catalytic and inhibitory mechanisms [113][114][115][116][117][118]. In addition, site-directed mutagenesis of GH1 enzymes with and without experimentally determined structures has been done to test the roles of various residues.…”
Section: Mechanism Of Substrate Binding and Specificitymentioning
confidence: 99%
“…However, a structure exists for a β-glucosidase from the thermophilic organism Thermotoga maritima similar to the wild-type C. saccharolyticus enzyme (47% similarity at the amino acid level). The proposed catalytic residues involved in the hydrolysis of the β-1,4-glycosidic bond are two glutamate residues-one acts as the nucleophile and the other as the acid/base [23]. These residues are highly conserved in this enzyme family, supporting their proposed catalytic role and the probable catalytic residues of the C. saccharolyticus β-glucosidase would be the Glu192 (acid/base) and Glu390 (nucleophile).…”
Section: Discussionmentioning
confidence: 82%
“…4,10,11,39 The glucose binding site has been established using, for example, 2-Fglucose derivatives of substrates and appears to be well-conserved for all GH1 β-glucosidases. 5,40,41 The involvement of the two glutamate residues in catalysis, one acting as a nucleophile and the other as an acid/base, has been established using various approaches, including mutagenesis and inhibitor studies, [42][43][44] and confirmed in several GH1 enzymes for which the 3D structure is known. 10,12,22,39,45,46 The nature of the amino acids forming the glucose binding site of hCBG is highly similar to other family 1 enzymes.…”
Section: The Active Site Pocket Of Hcbg and Comparison With Other Gh1mentioning
confidence: 99%